High-temperature oxidation behavior of polymer-derived SiHfBCN ceramic nanocomposites. Issue 12 (September 2016) - Yuan, J.; Galetz, M.; Luan, X.G.; Fasel, C.; Riedel, R.; Ionescu, E.
Abstract: Within this study, the oxidation behavior of SiHfBCN ceramic powders and monoliths was studied at temperatures from 1200 to 1400 °C. Both powder and monolithic samples exhibited parabolic oxidation behavior characterized by very low rates (10 −9 –10 −8 mg 2 cm −4 h −1 ). The activation energy of 112.9 kJ mol −1, which was determined for the SiHfBCN powder, is comparable to that of other silica formers such as silicon or SiC and relates to the diffusion of molecular oxygen through silica scale. Whereas, the values determined for the SiHfBCN ceramic monoliths (174 and 140 kJ mol −1, depending on the Hf content) indicate the complex nature of their oxidation process, leading at temperatures below 1300 °C to a continuous oxide scale consisting of borosilicate, silica, m -and t -HfO2 . At higher temperatures, the oxide scale consists of silica, HfSiO4 as well as m -and t -HfO2 and becomes discontinuous, probably due to the evaporation of boria.